2020
DOI: 10.1016/j.ijscr.2020.09.078
|View full text |Cite
|
Sign up to set email alerts
|

A case report on spontaneous hemoperitoneum in COVID-19 patient

Abstract: Highlights Young adult COVID-19 patient presented with acute abdomen. Evaluation of patient revealed splenomegaly, splenic rupture and hemoperitoneum. Patient recover with conservative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 18 publications
1
27
0
2
Order By: Relevance
“…Finally, this case series besides other intraperitoneal bleeding reports in COVID-19 patients [10,11,20,21] demonstrated that COVID-19 coagulopathy and AT should be studied more. To reduce the disease mortality and morbidity investigations on the pathophysiology of COVID-19-associated coagulopathy and finding the best intervention to prevent or treat it is needed.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, this case series besides other intraperitoneal bleeding reports in COVID-19 patients [10,11,20,21] demonstrated that COVID-19 coagulopathy and AT should be studied more. To reduce the disease mortality and morbidity investigations on the pathophysiology of COVID-19-associated coagulopathy and finding the best intervention to prevent or treat it is needed.…”
Section: Discussionsupporting
confidence: 53%
“…This marks one of the major differences between SARS-CoV-2-related splenic ruptures and other infectious and hematologic etiologiesthese result in splenomegaly in approximately 55% of cases [17]. Several case reports on spontaneous splenic rupture in patients with SARS-CoV-2 [17,18] as well as splenic thromboembolic disease have surfaced within the last year [4,[19][20][21]. We present a case of an elderly woman whose initial COVID-19 presentation at the hospital involved atraumatic/spontaneous splenic rupture in the absence of respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome (SARS) coronavirus-(CoV-) 2 (SARS-CoV-2), the etiological agent that causes coronavirus disease 2019 (COVID- 19), which was declared a pandemic by the World Health Organization (WHO) in March 2020, presents principally as a lower respiratory tract infection, but the multisystemic nature of the disease is evident in severe cases. Indeed, a broad spectrum of symptoms associated with COVID-19 has been identified.…”
Section: Introductionmentioning
confidence: 99%